The effect of Silicon di oxide Nano -Fillers reinforcement on some properties of heat cure polymethyl methacrylate denture base material - Hasanen A Alnamel; Mohammed Mudhaffer (College of Dentistry/ University of Baghdad, 2014)
Background: The purpose of this study was to evaluate the effect of addition of surface treated silicon dioxide Nano filler (SiO2) on some properties of heat cured acrylic resin denture base material (PMMA). The properties were impact strength, transvers strength, and surface hardness. Materials and methods: In addition to controlled group SiO2 powder was added to PMMA powder by weight in three different percentages 3%, 5% and 7%, mixed by probe ultra-sonication machine.120 specimens were constructed and divided into 3 groups according to the test (each group consist of 40 specimens) and each group was subdivided into 4 sub-groups according to the percentage of added SiO2 (finally each subgroup consist of 10 specimens). The tests conducted were impact strength (charpy test), transverse strength and indentation hardness (shore D). Results: A highly significant increase in impact strength and transverse strength was observed with the addition of SiO2 powder to (PMMA) at the percentage of 3% and 5%; while a significant reduction occurred in both impact and transverse strength specimens tests at the percentage of 7% A Highly significant increase in surface hardness was observed at the percentage of 3%, 5%and7. Conclusion: The addition of Nano SiO2 powder to acrylic resin improves the impact strength and transverse strength of acrylic resin at the same time this addition increase surface hardness with the increase in the concentration of Nano SiO2 particles.